Epidemiological assessment of parasitic zoonoses in Malaysia - Shekhar, K.C. (1991)
Food-borne parasitic zoonoses are emerging as major public health problems in most countries because they are widespread and pose a medical challenge. Not only are they important from an economic standpoint, but they also cause severe sequalae in all those affected. The extent of parasitic zoonoses in Malaysia is considered a "tip of the iceberg" problem. Cases of zoonotic diseases, like porocphaliasis, sarcocystosis, toxoplasmosis, cysticercosis, hydatidosis, echinostomiasis, and gnathostomiasis are traced and documented. An epidemiologic reassessment of methods is suggested to determine the extent of these parasitoses in Malaysia.